INFLUENCE OF PRODUCT INNOVATION STRATEGIES ON GROWTH OF SMALL AND MEDIUM WATER BOTTLING ENTERPRISES IN KENYA - Ndegwa, Kimani; Karanja Ngugi, Dr. Patrick; Mwangi Muturi, Dr. Willy (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
In Kenya, the SMEs in bottled water businesses are not growing as expected. This is shown by failure of water bottling firms to meet the demand of bottled water products. The increase in demand which grew by over 12 percent is not in tandem with growth of water bottling businesses with sales turnover increasing by only 3 percent. The study found strong relationship between product strategies and growth of SME water bottling firms in Kenya. . One of the major implications of this research is that firms can increase sales by offering the right marketing tools. Therefore organizations should carefully plan their marketing strategies, and allocate adequate marketing budget giving preference to the more effective tools. The SME water bottling entrepreneurs should also build capacity on the entrepreneurial marketing strategies to apply in their businesses and invest more in web based technology and infrastructure.